(untitled) (Med Phoenix, 2022)
Cadaveric dissection has been used for centuries to explore anatomy. The role of dissection in modern medical curricula has been a topic of intense debate. Anatomical education has been undergoing reforms in line with the demands of medical profession. Despite the rise of modern technology and evolved teaching methods, dissection continues to remain a cornerstone of the anatomy curriculum. Dissection helps to build discipline independent skills which are essential requirements of modern healthcare setup. Its utility is also reflected in the perception of students who believe that dissection provides them a foundation to develop clinical skills. Objections to the use of cadavers had led to other alternatives including virtual dissection of computer models. The current state of dissection in anatomy is deteriorating. Present study aims to assess the importance of traditional method like cadaveric dissection in teaching and learning anatomy at the present time when medical schools are inclining towards integrated and clinical application of learning methods.